AOFAS Position Statement Regarding Patient-Reported Outcome Measures. (December 2018) - Kitaoka, Harold B.; Meeker, James E.; Phisitkul, Phinit; Adams, Samuel B.; Kaplan, Jonathan R.; Wagner, Emilio
Outcome measures evaluate various aspects of patient health, and when appropriately utilized can provide valuable information in both clinical practice and research settings. The orthopedic community has placed increasing emphasis on patient-reported outcome measures, recognizing their value for understanding patients' perspectives of treatment outcomes. Patient-reported outcomes are information directly reported by patients regarding their perceptions of health, quality of life, or functional status without interpretation by healthcare providers. The American Orthopaedic Foot & Ankle Society (AOFAS) supports the use of validated patient-reported outcome (PRO) instruments to assess patient general health, functional status, and outcomes of treatment. It is not possible to recommend a single instrument to collect quality orthopedic data as the selection is dependent on the population being examined and the question being asked. We support the use of the PROMIS Physical Function Computerized Adaptive Test (PF CAT) or Lower Extremity Computerized Adaptive Test (LE CAT), which can be assessed with other domains such as Pain Interference. In addition, a disease-specific measure can be used when available.